2017
DOI: 10.1016/j.aott.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the lesser tuberosity for reverse Hill-Sachs lesions after neglected posterior dislocations of the shoulder: A retrospective clinical study of 13 cases

Abstract: ObjectiveThis study aimed to present middle-term functional and radiological outcomes of the transfer of the lesser tuberosity in the management of reverse Hill-Sachs lesions following posterior dislocations of the shoulder.Patients and methodsWith a diagnosis of neglected posterior shoulder dislocation (8 locked, 5 recurrent), 13 male patients (age range: 28–72; mean age: 39.3 years) who underwent the transfer of the lesser tuberosity due to reverse Hill-Sachs lesions, were retrospectively reviewed based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…In another study, Demirel et al investigated the middle-term functional and radiological outcomes of the transfer of the lesser tuberosity in the management of reverse Hill–Sachs lesions following posterior dislocations of the shoulder. 31 They reported satisfactory results at the last follow-up of 13 patients treated in an open manner. In a case report of a young male athlete with neglected locked posterior shoulder dislocation combined with reverse Hill–Sachs lesion, Steckel et al illustrated excellent clinical, functional, and radiological outcome after open modified McLaughlin's procedure 32 Finally, in another case report, Charalambous et al described a modification of the open repair through deltopectoral approach and plication of the subscapularis tendon into the reverse Hill–Sachs lesion via two-bone anchors.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, Demirel et al investigated the middle-term functional and radiological outcomes of the transfer of the lesser tuberosity in the management of reverse Hill–Sachs lesions following posterior dislocations of the shoulder. 31 They reported satisfactory results at the last follow-up of 13 patients treated in an open manner. In a case report of a young male athlete with neglected locked posterior shoulder dislocation combined with reverse Hill–Sachs lesion, Steckel et al illustrated excellent clinical, functional, and radiological outcome after open modified McLaughlin's procedure 32 Finally, in another case report, Charalambous et al described a modification of the open repair through deltopectoral approach and plication of the subscapularis tendon into the reverse Hill–Sachs lesion via two-bone anchors.…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that performing a modified McLaughlin procedure is enough [ 13 , 14 ]. They reported good results, in terms of joint stability, simply eliminating shoulder internal rotation postoperatively, with the use of either in an abduction brace and neutral rotation or in an external rotation brace [ 13 , 14 ]. However, if joint stability and posterior labrum pathology are not addressed intraoperatively, the joint stability postoperatively relies mostly on the patient’s compliance to a shoulder brace avoiding internal rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative treatment is an option ("supervised neglect"), especially in low-demand elderly patients with concomitant comorbidities, however, in the vast majority of the patients (the young and active ones as most of them are) various operative options have been suggested [11]. A reverse Hill-Sachs lesion with impaction of more than 20-40% of the humeral head articular surface and symptoms of posterior instability or pain, usually needs to be addressed surgically [12][13][14]. Bone disimpaction and fracture fixation, reconstruction with muscle-tendon transfer (McLaughlin procedure or a modified technique), rotational osteotomy, humeral bone augmentation (using autograft, allograft, or a synthetic substitute), arthroscopy and posterior Bankart repair or even joint arthroplasty, are all viable options in the acute phase, depending on the various clinical and radiological parameters [11,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…With 58% of capsulolabral lesions and 28% of engaging RHSLs, 12 posterior shoulder dislocation often leads to posterior instability. Most studies on the treatment of RHSLs are Technical Note,8, 9, 10 and only a few have evaluated outcomes3, 13; none have evaluated the outcomes of arthroscopic remplissage of the defect.…”
Section: Discussionmentioning
confidence: 99%